Cytotoxic oligophenols from the rhizome of Wikstroemia indica. Issue 4 (15th February 2018) - Wang, Qirui; Jiang, Yiping; Luo, Chaohua; Wang, Ruichen; Liu, Sui; Huang, Xiaojun; Shao, Meng
Graphical abstract: Abstract: A new tricoumarin glycoside, triumbelletin-7- O -β-d -glucoside (1 ) and a new biflavonoid, wikstroflavone A (2 ), together with two known compounds, wikstaiwanone A (3 ) and wikstaiwanone B (4 ), were isolated from the rhizome of Wikstroemia indica . The structures of new compounds were elucidated by extensive spectroscopic techniques (UV, IR, HRESIMS, 1D, 2D NMR and CD), in combination with quantum chemical calculations of 13 C NMR and ECD spectra. All isolates were tested for their antineoplastic activities against cancer-derived cell lines HCT116, SW480, U87 and T98G. Compounds2 –4 exhibited moderate cytotoxic activities to the four cell lines. The flow cytometry assay and western blot analysis revealed that the cytotoxic effects were possibly attributed to the induced apoptotic cell death.